Adoption of prasugrel into routine practice: rationale and design of the Rijnmond Collective Cardiology Research (CCR) study in percutaneous coronary intervention for acute coronary syndromes - Yetgin, T. (Bohn Stafleu van Loghum, 2013)
BACKGROUND: Platelet inhibition is crucial in reducing both short- and long-term atherothrombotic risks in patients with acute coronary syndromes (ACS) managed with percutaneous coronary intervention (PCI). Based on randomised trials, recent recommendations in the current guidelines include the endorsement of prasugrel as a first-choice adenosine diphosphate receptor inhibitor. Yet, there is limited experience with the use of prasugrel in routine practice. METHODS: The Rijnmond Collective Cardiology Research (CCR) registry is a prospective, observational study that will follow-up 4000 PCI-treated ACS patients in the larger region of Rotterdam, the Netherlands. Based on recently implemented hospital protocols, all patients will receive prasugrel as first-choice antiplatelet agent, unless contraindicated, in accordance with European guidelines, and will be followed for up to 1 year post-discharge for longitudinal assessment of outcomes and bleeding events. This registry exemplifies a collaborative study design that employs a regional PCI registry platform and provides feedback to participating sites regarding their practice patterns, thereby supporting and promoting improvement of quality of care. CONCLUSION: The CCR registry will evaluate the adoption of prasugrel into routine clinical practice and thus, will provide important evidence with regard to the benefits and risks of real-world utilisation of prasugrel as antiplatelet therapy in PCI-treated ACS patients.